Bridging the gap between research and clinical practice – a new initiative. Issue 4 (14th September 2016) - Ciapala, Joanna; Mullins, Bradley; Forrest, Alexandra; Molodynski, Andrew
Abstract : Research is critical in advancing health care and improving outcomes for patients. The NHS constitution 1 pledges to inform patients of research that they may be eligible to participate in. However, this often does not occur and can be particularly challenging in mental health services, with a number of barriers causing difficulties. Here the authors explore some of the reasons for difficulties in recruiting patients to mental health studies and offer a potential solution.